Experimental thermal performance evaluation of a horizontal ground-source heat pump system - Inalli, M; Esen, H (Pergamon-Elsevier Science Ltd, 2004)
The goal of the present study is to validate the effects of the parameters such as the buried depth of earth coupled heat exchanger, mass flow rate of the water-antifreeze solution and sewer water on the performance of a horizontal ground-source heat pump (GSHP) system used for space heating experimentally. The GSHP system connected to a test room with 16.24 m(2) floor area in Firat University, Elazig (38.41degreesN, 39.14degreesE), Turkey, was designed and constructed. The heating and cooling loads of the test room were 2.5 and 3.1 kW at design conditions, respectively. The experimental results were obtained from November to April in heating season of 2002-2003. The average performance coefficients of the system (COPsys) for horizontal ground heat exchanger in the different trenches, at 1 and 2 m depths, were obtained to be 2.66 and 2.81, respectively. Results obtained from experimental measurement concluded that the horizontal GSHP systems can be used for Elazig, Turkey climatic conditions. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: ground-source heat pump; horizontal heat exchanger; sewer water; coefficient of performance (COPsys); space heating